Heavy metal removal from industrial wastewater using parkia speciosa pod - Vanithaa, Ponnaiah (2017)
Heavy metals normally caused by manufacturing, agriculture, sewage and motor vehicle emission have been a main reason for polluted rivers nowadays. The common wastewater treatment that been done in Malaysia are chemical precipitation and reverse osmosis. Even both methods are commercialized, they are expensive. To cut cost, adsorption method can be implemented to reduce the heavy metals that polluted the river. Parkia speciosa pod which is known as stink bean or ‘petai’, is one of the agricultural waste which can be used as activated carbon to remove the heavy metal in industrial waste water. By adapting the views and methods from the journal, the percentage of copper and zinc contaminating the wastewater was tested. The Parkia Speciosa pod was obtained, cut, washed and dried in oven. Later the pod was grounded into powder and burnt in furnace. The product was later tested contact time and size of particle. The aim of this research is to determine the effect of size and effect of contact time in reducing the percentage of heavy metal mainly copper and zinc in water sample. The size used are 1.18 mm, 600 micron and powder form activated carbon from Parkia Speciosa pod. The contact time tested was 4 weeks. As the treatment goes, the content of zinc was reducing drastically and on week two where 1.18 mm removed about 95% of zinc ,600 micron about 99% of zinc and powder about 100% of zinc. On the third week, all the sizes removed 100% of the zinc present in water. The content of copper was reducing drastically and on week two where 1.18 mm removed about 71% of zinc ,600 micron about 98% of copper and powder about 100% of copper. On the third week, all the sizes removed 100% of the copper present in water. The zinc, copper and COD drop drastically during the treatment proving longer period of contact able to remove all inorganic matter in water by conducting this study, the amount of zinc and copper that contaminated the wastewater was reduced and this is one of the cheapest method that can be used in wastewater treatment.